PENGARUH BERBAGAI KONSENTRASI GLUTAMIN TERHADAP PERTUMBUHAN TUNAS Aquilaria malaccensis Lamk. SECARA KULTUR JARINGAN - Chrisnanda Ayu Melati; Etty Handayani; Toni Herawan (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2021)
Aquilaria malaccensis Lamk. is a type of plant that is threatened with extinction due to the high level of illegal collection from the forest. Tissue culture techniques provide an alternative to vegetative propagation on a large scale for conservation efforts. The addition of glutamine to the culture media was intended to increase the growth of A. malaccensis Lamk shoots. The research was conducted with quantitative research methods using single factor laboratory experiments with four (4) treatments arranged in a completely randomized design (CRD). The treatments were differentiated based on the addition of glutamine, namely, G0: 0 mg / l; G1: 10 mg / l; G2: 20 mg / l; G3: 30 mg / l. Data analysis used Analysis of Variance (Annova) with a level of α = 5%. The results showed that Glutamine could't affect the growth of A. malaccensis Lamk, but there was the best trend in the addition of Glutamine 20 mg/l.